La planification stratégique spatialisée contribue-t-elle à la durabilité territoriale ? La limitation des consommations foncières dans les schémas de cohérence territoriale à Marseille-Aix, Nantes Saint-Nazaire, Rennes et Tours - José Serrano; Christophe Demazière; Fabien Nadou; Sylvie Servain (Développement Durable et Territoires)
This article focuses on how spatial strategic planning attempts in the French context, to regulate land consumption due to business sites. It is based on the analysis of planning documents, interviews and map analysis on the territory of four French urban areas: Aix-Marseille, Nantes Saint-Nazaire, Rennes and Tours. Section 1 recalls the legislator’s intentions in spatial planning and intermunicipal cooperation. Section 2 presents the case study regions and the methodological device. Sections 3 and 4 present the analysis of economic development strategies and development planning documents. We conclude that intermunicipal cooperation is a key variable to account for the limitation of land consumption across large urban regions.